2022
DOI: 10.3390/app12199825
|View full text |Cite
|
Sign up to set email alerts
|

Foot Anatomical Structural Variations Increase the Risk of Falls in Older Adults

Abstract: Falls are common among older adults. The purpose of this study was to demonstrate the relationship between foot anatomical structural variations and balance in older adults and quantify foot posture and stabilometry as predictors of fall risk. This case-control study of older adults classified cases or controls according to falls in the last five years. All subjects were healthy women and men > 65 years old (n = 164), who were divided into two groups: 83 individuals who had suffered from a fall in the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…While direct evidence linking the foot arch index to sagittal and frontal balance is limited, some studies have explored the relationship between foot arch characteristics and balance control. For instance, 35 demonstrated that the anatomical structure of the foot is essential in assessing balance conditions, particularly in the elderly population. It was observed that elderly individuals exhibit lower hallux mobility and increased forefoot width compared to younger individuals, where the foot tends to be flatter and more pronated.…”
Section: Discussionmentioning
confidence: 99%
“…While direct evidence linking the foot arch index to sagittal and frontal balance is limited, some studies have explored the relationship between foot arch characteristics and balance control. For instance, 35 demonstrated that the anatomical structure of the foot is essential in assessing balance conditions, particularly in the elderly population. It was observed that elderly individuals exhibit lower hallux mobility and increased forefoot width compared to younger individuals, where the foot tends to be flatter and more pronated.…”
Section: Discussionmentioning
confidence: 99%